1990
DOI: 10.1037/0278-7393.16.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Semantic priming and repetition priming from masked words: Evidence for a center-surround attentional mechanism in perceptual recognition.

Abstract: Two lexical decision experiments compared semantic and repetition priming by masked words. Experiment 1 established prime-mask stimulus onset asynchronies (SOAs) with presence-absence detection judgments. Primes presented at detection-threshold SOAs produced equal facilitation for repeated and semantically related targets: 26 ms and 24 ms. Experiment 2 established SOAs with semantic judgments. Primes presented at 70% of the semantic-threshold SOA to mimic the exposure conditions of Experiment 1 produced slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
188
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(214 citation statements)
references
References 44 publications
(98 reference statements)
22
188
4
Order By: Relevance
“…This RT pattern was similar to that found by Cave and Zimmerman (1997). They showed that when attention selects an object in the visual field, a suppressive surround centered on the object location is initiated, providing the first behavioral evidence of the flanking inhibition phenomenon (see also Carr & Dagenbach, 1990). Likewise, Walley and Weiden (1973) had originally proposed that, to avoid information overload, a lateral inhibition mechanism is involved in attentional selection.…”
Section: Resultssupporting
confidence: 53%
“…This RT pattern was similar to that found by Cave and Zimmerman (1997). They showed that when attention selects an object in the visual field, a suppressive surround centered on the object location is initiated, providing the first behavioral evidence of the flanking inhibition phenomenon (see also Carr & Dagenbach, 1990). Likewise, Walley and Weiden (1973) had originally proposed that, to avoid information overload, a lateral inhibition mechanism is involved in attentional selection.…”
Section: Resultssupporting
confidence: 53%
“…One theoretical approach that could be extended to account for the present results has been proffered by Carr and Dagenbach (1990) and Dagenbach and Carr (1994). By their "center-surround" account, when subjects have difficulty in their attempt to retrieve the meaning of a masked word, they focus their attention on that word's representation (the "center"), with the result that the meanings of semantically similar words (the "surround") receive lateral inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that even at short prime-target intervals priming observed for words presented in prime-target pairs might to a certain degree also depend upon controlled priming mechanisms (Shelton & Martin, 1992). Moreover, the effects of automatic spreading of activation and strategic attentional processing are most likely not independent (Balota et al, 1992;Carr & Dagenbach, 1990). Nevertheless, the relative contribution of automatic spreading of activation is generally assumed to be larger at short than at long SOAs, whereas the opposite holds for controlled priming mechanisms, such as expectancy generation and semantic matching .…”
Section: Discussionmentioning
confidence: 99%